Influence of the bleaching agent and adhesive system on the bond strength of the restorative material to intracoronary dentin - João Felipe Bonatto Bruniera; Aline Evangelista Souza-Gabriel; Melissa Andrea Marchesan (Revista Sul-Brasileira de Odontologia, 2013)
The bond strength of dentin bleached with high concentrated agents can be reestablished if the appropriate restorative material is selected. Objective: The aim of this study was to evaluate the influence of bleaching agents and adhesive system on bond strength of restorative material to intracoronary dentin. Material and methods: 60 fragments of intracoronary dentin (25 mm2) were embedded in acrylic resin and divided into 3 groups (n = 10): GI – not bleached (control), GII – 35% hydrogen peroxide (35HP), GIII – 38% hydrogen peroxide (38HP). The gel was applied for 10 min onto the dentin surface. This protocol was repeated three times at a single session. After 14 days, the groups were divided into subgroups according to the adhesive system used in the restoration: A – Self-etching (Clearfil SE Bond) and B – Total etching (Single Bond 2). The fragments were restored with Z100 Filtek resin using a bipartite matrix. After 24 h, the specimens were subjected to shear bond strength test. Data were analyzed by two-way ANOVA and Tukey test (p < 0.05). Results: The group bleached with 38HP (6.02 ± 3.95) had the highest bond strength to dentin, followed by 35HP (5.36 ± 3.54), and control group (3.11 ± 2.71) (p < 0.05), although without statistically significant differences. It was also verified a higher bond strength in the group restored with the self-etching adhesive system (6.60 ± 4.18) when compared to the total etching system (3.06 ± 1.57). Conclusion: When performing the restoration of teeth bleached with hydrogen peroxide at high concentrations (35% and 38%), self-etching adhesive system should be the first choice.